Air dalam Perspektif Hadis - Amiruddin, Andi Muhammad Ali (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
Water and related issues around its management and treatment, and behaviour of human beings towards water has been discussed in several disciplines including Islamic studies. Water has been playing a key role in Islam, whether for cleaning, bathing or ablution to prepare Muslims before doing religious rituals, such as praying and reading the Quran. Such an important role of water in Islam, however, has been payed less attention, particularly on its social and environmental treatment among Muslims. In order to raise awareness on this issue, this paper will particularly explore water treatment from the perspective of hadith or prophetic tradition. The main question to answer is how the prophetic hadiths respond towards water treatment, particularly on the issue of water pollution and how the Prophet was providing advice on this issue. This paper traces all water related hadiths and classifies them into several categories. The result shows that hadiths on water and how Muslims should behave towards water treatment has indeed been found in many canonical books of hadiths and they in turn should be referred by Muslims for better water management and treatment.